Pengaruh Nilai Tukar, Inflasi Dan Harga Minyak Dunia Terhadap Harga Saham Perusahaan Migas Pada Masa Pandemi Covid-19 - Ikhsani, Cindy Orlanda; Rosita, Irda; Rissi, Dita Maretha (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2023)
This study aims to determine the effect of exchange rates, inflation and world oil prices on oil and gas company stock prices during the Covid-19 pandemic. The sample in this study were 12 oil and gas companies that were listed on the IDX and published financial reports for 2020 and 2021. This research was conducted during the Covid-19 pandemic, namely from April 2020 to October 2021. The data analysis technique used in this study was regression analysis multiple linear with the help of SPSS 25 and WarpPls 3.0. The results of this study indicate that inflation and the exchange rate did not affect the share prices of oil and gas companies during the Covid-19 pandemic, while oil prices did affect the share prices of oil and gas companies during the Covid-19 pandemic with a positive path coefficient value.